Chiral NADH Model: Design, Synthesis, Asymmetric Reduction Reaction, and Fluorescence Characteristics - Bai, Cui-Bing; Zhang, Lei-Yang; Wang, Nai-Xing; Yan, Zhan; Wu, Yue-Hua; Xu, Bao-Cai; Liu, Ning; Wang, Bo-Zhou; Tomasic, Vesna (Letters in Organic Chemistry, 2022)
A new type of NADH model compound, which has six asymmetric carbon centers, has been synthesized by an efficient and convenient method. We used NADH models combined with enzymes in the asymmetric reduction. It was the first time that dehydrogenase combined with NADH models instead of inorganic catalysts, such as MgCl2, was used in the asymmetric reduction. Furthermore, the experimental results showed that the new NADH model has the strongest fluorescence emission properties compared to previously reported models.
Keywords: synthesis